2023
DOI: 10.5194/acp-2022-849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Airborne observations of the surface cloud radiative effect during different seasons over sea ice and open ocean in the Fram Strait

Abstract: Abstract. This study analyzes the surface cloud radiative effect (CRE) obtained during airborne observations of three campaigns in the Arctic north-west of Svalbard. The surface CRE quantifies the potential of clouds to modify the radiative energy budget of the surface and is calculated by combining broadband radiation measurements during low-level flight sections in mostly cloudy conditions with radiative transfer simulations of cloud-free conditions. The significance of surface albedo changes due to the pres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Reducing the uncertainty is of primary interest, as clouds play a crucial role in several feedback mechanisms . In particular, clouds exert a strong control on the Arctic surface radiative energy budget (Intrieri et al, 2002;Becker et al, 2023). Clouds have a cooling impact by reducing the incoming solar radiation and a warming effect by emitting thermal-infrared (TIR) radiation (Shupe and Intrieri, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing the uncertainty is of primary interest, as clouds play a crucial role in several feedback mechanisms . In particular, clouds exert a strong control on the Arctic surface radiative energy budget (Intrieri et al, 2002;Becker et al, 2023). Clouds have a cooling impact by reducing the incoming solar radiation and a warming effect by emitting thermal-infrared (TIR) radiation (Shupe and Intrieri, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Williams and Igel (2021) and Morrison et al (2008) showed that droplet number concentration (N d ) impacts the optical properties of clouds. The interaction of clouds with surface albedo and temperature has been studied over the Arctic sea ice (Curry and Ebert, 1992;Walsh and Chapman, 1998;Intrieri et al, 2002;Walden et al, 2017;Stapf et al, 2020), open ocean (Wendisch et al, 2023b;Becker et al, 2023), and land (Dong et al, 2010;Miller et al, 2015;Ebell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation